Norm and Normality, Starting from Merleau-Ponty - Spina, Marco (Phenomenology and Mind, 2016)
The present work pursues two main objectives. The first is to pinpoint, by means of a series of philosophical arguments, the meaning of the word “norm” and, specifically, to explain the tension between normality and normativity in detail. The second, closely related to the former, hinges on Merleau-Ponty’s personality, and aims at putting the “space” of the norm and the key notion of normality in a new form, starting from some essential elements of his writing. This effort is particularly significant in The structure of Behavior, Phenomenology of Perception and in The Primacy of Perception and its Philosophical Consequences.